Hijriyah Months and The Construction of Religious Moderation in The Sombaopu Community of Gowa, South Sulawesi - Alimuddin, Alimuddin (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research examines the response of the people of Sombaopu District, Gowa Regency, South Sulawesi in responding to difference views in determining the beginning of the Hijriyah (Islamic lunar calendar) months. This issue needs special attention because it holds the potential for internal conflict among Muslims. This research is classified as descriptive qualitative field research. The aim is to obtain an overview of social phenomena that exist among the Muslim community in Sombaopu District, Gowa Regency, South Sulawesi Province. This research focuses on the public's response to differences in determining the beginning of the Hijriyah months which is connected to the concept of religious moderation as an effort to prevent society from extreme understandings and practices that are not in accordance with religious guidelines and regulations. This research concludes that religious moderation can be a solution in preventing the emergence of social conflict while strengthening the sense of unity and integrity in society. The success of this effort can be achieved more quickly if the relevant parties, especially government institutions, religious organizations and community leaders are actively involved in this activity.